Additional Psychometric Data for the Mate Value Scale. (26th July 2016) - Gillen, Meghan M.; Collisson, Brian; Murtagh, Michael; Browne, Blaine L.; McCutcheon, Lynn E.
Abstract : We administered a revised version of the Mate Value Scale that focuses on individuals' perception of their romantic partner's mate value. Students ( N = 330) from four universities completed surveys. The measure demonstrated good internal consistency reliability. Multiple regression analyses indicate that those who perceive their mates as possessing a higher value tended to compromise more when faced with conflict with their partners, had less anxiety in close relationships, and had more passionate love attitudes. We argue that this pattern of associations provides additional validity data in support of the Mate Value Scale.